Crossroads between Islamic spirituality and the instruction of science - Machouche, Salah; Bensaid, Benaouda; Ahmed, Zuraida (2019)
The increased interest in understanding the influence of spirituality on the diverse domains of life, and alongside, the inherent pathways with science continues to draw the interest of both academicians and professionals. In the context of Muslim communities, however, and in view of their struggle for educational reforms, this issue is considered as highly critical, given Muslim active spiritual and religious take on life. This preliminary study explores the linkages associating Muslim spirituality to science and its instruction. This research shows that for science instruction, spirituality is naturally interconnected with science, helps broaden the horizon of exploration, nurtures Muslims’ connection with the divine, and helps refine their ethical responsibility towards society and nature. Further empirical research on the effects of spirituality on students’ learning attitudes to sciences and instructors’ delivery would bring to light how Muslim spiritual values shape current personal and educational developments.